ANALISIS PHBS DI TEMPAT KERJA PUSKESMAS - Yulizar Sukma Rani; Ajeng Nurika Putri, Febi Aprillia Sinaga, Syesar Qandias Sadin, Shakinah Mawaddah, Nur Fitriani, Ahm (Jurnal Kesehatan, 2023)
Clean and healthy living behavior in the workplace, fostering a healthy and comfortable work environment, reducing sick absence rates, increasing work productivity are the goals of K3 promotion. With the large potential for danger, it is necessary to implement the K3 program at the puskesmas as a step to ensure the work safety of health workers. This study aims to describe the perception of PHBS after the puskesmas employees participate in socialization and what is to be achieved is to increase workers' knowledge about the importance of PPE and increase knowledge of CTPS in the workplace environment. This research was made using the Systematic Literature Review (SLR) method. The SLR method is used to identify, assess, evaluate, and interpret all available research on the topic of PHBS at the Puskesmas. By using the SLR method, it is possible to systematically review and identify journals. The research results also explain that PHBS activities have begun to be implemented in society such as washing hands, wearing masks, and maintaining distance. However, several PHBS violations were still found, and in research that there was a positive correlation both directly and indirectly from attitudes, subjective norms, perceptions of behavioral control, and intentions towards implementing PHBS.